GSK-3β inhibition alleviates arthritis pain via reducing spinal mitochondrial reactive oxygen species level and inflammation. - He-Yu Yang; Xu Sun; Shu-Qing Zhen; Liang-Zhu Yu; Jie-Qiong Ding; Ling Liu; Min Xie; Hai-Li Zhu (PLoS ONE, 2023)
Pain is the main symptom of osteoarthritis, which severely reduces the patients' quality of life. Stimulated neuroinflammation and elevated mitochondrial oxidative stress are associated arthritis pain. In the present study, arthritis model was established by intra-articular injection of complete Freund's adjuvant (CFA) on mice. Knee swelling, pain hypersensitivity and motor disability were observed in CFA-induced mice. In spinal cord, neuroinflammation was triggered and presented as severe infiltration of inflammatory cells and up-regulated expressions of glial fibrillary acidic protein (GFAP), nuclear factor-kappaB (NF-κB), PYD domains-containing protein 3 (NLRP3), cysteinyl aspartate specific proteinase (caspase-1) and interleukin-1 beta (IL-1β). Mitochondrial function was disrupted and characterized as elevated expressions of B-cell lymphoma 2 (Bcl-2)-associated X protein (Bax), dihydroorotate dehydrogenase (DHODH) and cytochrome C (Cyto C), and reduced expressions of Bcl-2 and Mn-superoxide dismutase (Mn-SOD) activity. Meanwhile, as a potential target for pain management, glycogen synthase kinase-3 beta (GSK-3β) activity was up-regulated in CFA induced mice. To explore potential therapeutic options for arthritis pain, GSK-3β inhibitor TDZD-8 was intraperitoneally injected for three days on CFA mice. Animal behavioral tests found that TDZD-8 treatment elevated mechanical pain sensitivity, suppressed spontaneous pain and recovered motor coordination. Morphological and protein expression analysis indicated that TDZD-8 treatment decreased spinal inflammation score and inflammatory related protein levels, recovered mitochondrial related protein levels, and increased Mn-SOD activity. In summary, TDZD-8 treatment inhibits GSK-3β activity, reduces mitochondrial mediated oxidative stress, suppresses spinal inflammasome response, and alleviates arthritis pain.